Advances in conceptual modeling - applications and challenges : ER 2010 workshops ACM-L, CMLSA, CMS, DE@ER, FP-UML, SeCoGIS, WISM Vancouver, BC, Canada, November 1-4, 2010 proceedings (Lecture Notes in Computer Science / editors Gerhard Goos, Juris Hartmanis, and Jan van Leeuwen ;, 2010)
This book constitutes the refereed proceedings of workshops, held at the 29th International Conference on Conceptual Modeling, ER 2010, in Vancouver, Canada, in November 2010. The 31 revised full papers presented were carefully reviewed and selected from 82 submissions. The papers are organized in sections on the workshops Semantic and Conceptual Issues in GIS (SeCoGIS); Conceptual Modeling of Life Sciences Applications (CMLSA); Conceptual Modelling of Services (CMS); Active Conceptual Modeling of Learning (ACM-L); Web Information Systems Modeling (WISM); Domain Engineering (DE@ER); and Foundations and Practices of UML (FP-UML).